A condição infantil em Sigmund Freud e sua dimensão ético-formativa - Cezar, Luciana Poleto Oltramari (2020)
The purpose of this research is to bring the contributions of psychoanalysis to the comprehension of the immature child condition, the processes of early psychic structuring and its formative ethical dimension. In this perspective, the role of the familiar in the subjective constitution of a child becomes priority, based on the assumption that this constitution occurs in intersubjectivity and that the construction of the human psyche goes through structuring times. This study is delimited in Freud’s texts that deal with the theme of early psychic constitution and the relationship with the figure of the caregive. This research proposes to think about what does mean, from a psychoanalytic point of view, the notion of the child as an immature being, what is inherent to the human condition. As psychoanalysis theoretically conceive the human psychic constitution from the notion of primordial helplessness and the action of the familiar – another human being, we will try to identify in Freud’s works the moments in which he presents ideas about the following indicators: the primordial helplessness, the presence of the familiar, child sexuality constitutive of the human condition and the formative ethical dimension resulting from the process of psychic structuring. The chosen texts are those that offers elements to compose the process of building these indicators, from the first topic of Freudian metapsychology. It is, therefore, about examining what needs to happen, in terms of psychic constitution for the construction of the psychic subject in the Freudian sense and why we consider that the inter-human encounter is potent from an ethical and formative point of view. The present research is of a qualitative nature, of bibliographic nature and makes use of the hermeneutic posture in the work with the classic texts of Sigmund Freud. The research problem is formulated as follows: How does the formative ethical dimension occur from the child condition and the process of early psychic structuring in Sigmund Freud? The results presented in this research is that the early constitution of a psyche and the humanization process take place in the loving bond with its primary caregivers based on the relations of pleasure and desire that drench the human encounter with eroticism as well as the necessairy drive waivers that grant the adult the position of alterity. Considering that vulnerability and dependence are inherent to the child condition, it was found the commitment of the adult and his primordial role in early childhood. In short, the human care plays an essential role in the child condition and, in a broader sense, for the ethical formation of human beings.